Humanity's Gain from Unbelief : Reprinted from the "North American Review" of March, 1889 - Bradlaugh, Charles, 1833-1891 (Salt Lake City, UT : Project Gutenberg, 2009)
"Humanity's Gain from Unbelief" by Charles Bradlaugh is a philosophical and polemic work written in the late 19th century. This book succinctly argues that the progress and well-being of humanity have been significantly enhanced by the rejection of religious dogmas, particularly those inherent in Christianity. Bradlaugh adopts a skeptical stance towards supernatural beliefs, positing that skepticism is essential for general progress, particularly in the realms of science and civil rights. In this comprehensive exposition, Bradlaugh contends that various societal advances, such as the abolition of slavery and improvements in the treatment of the mentally ill, are attributable to the rise of unbelief rather than the teachings of Christianity. He emphasizes that many historical figures who fought for human rights often acted in opposition to religious norms rather than in accordance with them. Through numerous examples, the author illustrates that as societies have increasingly embraced skepticism and rational inquiry, they have correspondingly diminished the influence of outdated beliefs, leading to societal advancements in morality, justice, and human rights. Hence, he posits that humanity has gained immensely from the very disbelief that has enabled freedoms and advancements. (This is an automatically generated summary.)
Release date is 2009-10-06
Produced by David Widger
Keywords: Free thought; Atheism